Biomechanical evaluation of anterior and posterior lumbar surgical approaches on the adjacent segment: a finite element analysis. Issue 14 (3rd July 2020) - Wang, Bingjin; Ke, Wencan; Hua, Wenbin; Lu, Saideng; Zeng, Xianlin; Yang, Cao
Abstract: The purpose of this study was to use models of spine to compare range of motion and intradiscal pressure of adjacent segments performing anterior and/or posterior lumbar surgical approaches and predict potential risk of adjacent segment degeneration. A previously validated finite element model of the intact L1-S1 segments was used. Three different anterior and one posterior surgical fixation approaches for tuberculosis were performed in L3-L5. Three different anterior surgical models were constructed according to the anterior approaches involving debridement, bone graft with or without titanium mesh, and internal fixation with different number of screws and rods. The posterior surgical approach involved transforaminal lumbar interbody debridement, bone graft, and internal fixation. Range of motion and intradiscal pressure of segments adjacent to the fusion were assessed, and biomechanical influences were compared. Intradiscal pressure and range of motion of the adjacent L2/3 and L5/S1 increased during different physiological movements after anterior and/or posterior surgical approaches as compared to baseline values. Comparison between the biomechanical values assessed after different anterior surgical approaches yielded no significant difference. After anterior and posterior surgical approaches were performed on the same model, there were no significant differences in intradiscal pressure and range of motion of the adjacent L2/3 and L5/S1. Anterior and/or posterior lumbar surgical approaches increased range of motion and intradiscal pressure in L2/3 and L5/S1, suggesting each lumbar surgical approach assessed has the potential risk of adjacent segment degeneration. However, there were no significant differences between the biomechanical measurements across the different surgical approaches evaluated.